A, The The Role Of Family Management In Theformation Of Children's Character : A Literature Review - Ahmad Subhan; Suhroji Adha (Sean Institute, 2024)
Family is one of the most important factors in a child's success. As a child grows and develops, the family becomes the natural foundation. The physical and psychological development of a child takes place within the family. This paper attempts to investigate the viewpoint of family management. The socio-culture of the family has undergone significant changes in the millennial era, which is characterised by the rapid development of technology and information. The speed of globalisation makes the industrial revolution 4.0 unstoppable. The results of analyses from various sources and references show that there is a need for adaptive strategies in family education given the constant changes of the times.